THE INFLUENCE OF HOMO IPHONE ON TRENDS, LIFESTYLE AND BUYING DECISIONS IN CASE STUDY ON GEN Z - Peptiana; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This article is a literature study that aims to understand the influence of "Homo iPhone" on trends, lifestyles, and purchasing decisions of generation Z. This study is expected to provide deeper insight into the interaction between technology trends, social identity, and consumer behavior of generation Z in choosing premium products such as the iPhone. The results of the study indicate that factors such as brand image, product quality, and iPhone technological innovation play a significant role in shaping purchasing decisions of young consumers. In addition, the digital lifestyle and strong social influence among generation Z also strengthen the appeal of the iPhone as a symbol of status and identity. The research object uses online libraries and other academic sources. The research method used is a quantitative method with literature studies sourced from scientific journals and open e-books.